E-LEARNING: NEW TASKS FOR THE UNIVERSITY TEACHER - Marina V. Zagvozdkina; Vladimir I. Stymkovsky (Высшее образование в России)
The article deals with the topical problem of updating the content of the University teaching under the new conditions of the educational environment of e-Pedagogy. The authors show how e-didactics changes the status and functions of a higher school teacher stimulating his (her) development towards improving the quality of education and the design of new models and learning technologies. The article describes the approaches to improve teaching activities in the new conditions of the educational environment, emphasizes the importance of an integrated approach inworking withopen educational resources. The core of the synergistic effect of forming a new generation of teachers the authors see in the matrix of skills and competences linking occupational, educational, social & ICT competences.